Framework para análise das tensões da base instalada no estabelecimento de uma infraestrutura de informação - Silva, Alandey Severo Leite da (2017)
The main objective of this work is to create an installed base tensions analysis framework and how they influence the establishment of an Information Infrastructure (II). Among some II examples are the Internet, e-commerce, Electronic Data Interchange, the wireless network infrastructure (wireless), integrated enterprise management systems (Enterprise Resource Planning - ERP), the interaction between people, the health sector and the scientific collaboration networks. Methodologically, a qualitative position and a more social and humanistic view of the subject were adopted to reach the understanding of its influence. For application of the built framework, Electronic Health Record (EHR) study data in the State of Paraíba were analyzed. In addition to the bibliographic sources consulted, the content analysis was used for the interpretation of collected interviews. The analysis through this framework points out that RES are complex and permeated by unresolved tensions, bordering on consolidation of a II, requiring practices that do not underestimate or neglect its installed base, its socio-technical effects, its stresses and its outward reversals. The application of the framework in other II can contribute to the improvement and consolidation of this instrument, making it more comprehensive and efficient in its purpose.